KERJASAMA MILITER VIETNAM â AMERIKA SERIKAT TAHUN 2010-2013 - , TIAN SATYANING KRISTANTI D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
After diplomatic normalization in 1995 until 2009, Vietnam â United Stateâs bilateral relation continued to grow and increase in some aspects, such as economic and social, except in defense/military relation. In 2010, Vietnam and United States started to develop and upgrade their defense relation by having military-to-military-level cooperation, formal defense dialogue, and signing formal military aggreements. United Stateâs ship visit to Vietnam in 2010 followed with some navy cooperations and activities became the sign of the beginning of their defense relation, because that was the first time for both countries to have military-to-military-level cooperation. This writing would like to explain that there is an external factor, which is the change in international system, that affects the characteristic in Vietnam and United Stateâs bilateral relation. That change, which is the rise of China, then boosted Vietnam and United States to increase their defense/military relation.